A Crawling Soft Robot Driven by Pneumatic Foldable Actuators Based on Miura-Ori - Meng Yu; Weimin Yang; Yuan Yu; Xiang Cheng; Zhiwei Jiao (Actuators, 2020)
Origami structures are highly demanded for engineering applications. Using origami folding to design and actuate mechanisms and machines offers attractive opportunities. In this paper, we design a crawling robot driven by pneumatic foldable actuators (PFAs) based on Miura-ori, according to the parallel foldable structure and different control patterns, which can perform different movements. The PFA inspired from Miura-ori is composed of a folding part, transition part, and sealing part, made by flexible materials and a paper skeleton. This actuator can obtain a large deformation by folding under negative pressure due to its own characteristics, and the relationship between deformation and pressure is analyzed. According to the different folding and unfolding times of left and right actuators, the crawling robot can perform both linear and turning movements. The speed of the robot is about 5 mm/s and it can turn at a speed of about 15°/s. The crawling robot uses the ability of the foldable structure to cope with the challenges of different environments and tasks.